The Role of Sharia-Compliant Hedging Instruments in Managing Sukuk Yield Volatility - Hasan, Jamaludin; Sarib, Suprijati; Lestari Niu, Fitria Ayu; Nuraini Kaida, Anisa Dwi (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2025)
The rapid expansion of Indonesia’s sukuk market has become a strategic pillar in the advancement of the national Islamic economic framework. Nevertheless, this progress is overshadowed by the inherent risk of yield volatility, primarily triggered by fluctuations in monetary policy. Such volatility generates significant cash flow uncertainty for issuers and price risks for investors. Unmitigated, this risk has the potential to hinder market deepening and constrain long-term financial stability.This study aims to conduct an in-depth analysis of the conceptual framework and technical mechanisms of Sharia-compliant hedging instruments as a viable solution to these challenges. Employing a systematic literature review with a qualitative analytical approach, the study synthesizes diverse academic works, industry standards, and relevant fatwas. The findings indicate that the Islamic Profit Rate Swap (IPRS) represents a manifestation of Sharia-compliant financial engineering that is theoretically effective in mitigating yield-related risks. Structured through a series of wa’d (unilateral promises) and tawarruq (commodity murabahah) contracts, the IPRS mechanism provides functional equivalence to conventional swaps by enabling market participants to exchange fixed-rate exposures for floating ones.The main contribution of this research lies in bridging the existing literature gap between global discourses on Islamic derivatives and their contextual application within Indonesia’s sukuk market. The study concludes that understanding and adopting sophisticated instruments such as the IPRS is not merely an option but a necessary condition for achieving maturity, resilience, and market completeness in the future development of the Islamic capital market.